Role of ferroelectric polarization during growth of highly strained ferroelectric materials - Rui Liu (Nature Portfolio, 2020)
Ferroelectric (FE) materials are used in a wide range of applications, which often requires sizable FE polarization. Here, the authors report a growth procedure to enhance the FE polarization by exploiting the polarization of a FE substrate during growth to obtain higher strains and polarizations in the final material.